N01 Fatigue and physical activity in individuals with inflammatory bowel disease: a feasibility cross-sectional, correlational study. (25th January 2019) - Farrell, D; Byron, C; Forry, M; Godwin, N; Judge, C
Abstract: Background: Fatigue is a problematic and burdensome symptom experienced by individuals with inflammatory bowel disease (IBD). The optimal management of fatigue remains poorly understood, with physical activity likely to be a beneficial way to manage the symptom. However, physical activity levels are reduced in patients with IBD compared with healthy controls. This study aims to investigate the relationship between fatigue and physical activity and intensity of activity in individuals with IBD. Methods: A multi-centred, cross-sectional, correlational feasibility study was employed. A consecutive sample of 21 patients with Crohn's disease or ulcerative colitis were recruited from two IBD centres in the Republic of Ireland. The IBD Fatigue scale was used to measure fatigue and triaxial accelerometers (ActiGraph wGT3X-BT) objectively measured physical activity levels and intensity of activity undertaken during seven consecutive days. Results: A moderate level of fatigue (IBDF Section 1 Md (IQR) = 11 (6–12)), predominantly intermittent in nature (76.2%) was reported by participants (81% female; 66.7% Crohn's disease; 71% active disease). On average, participants self-reported sleeping 9 h per night. Over the week, the intensity of activity was predominantly sedentary (Md 5 days, 19 h, 33 min) or light (Md 21 h, 44 min). The median moderate-to-vigorous intensity of physical activity per day was 36 min and step count over the week was 50, 732 steps. A strong, positive, statistically significant relationship was found between level of fatigue and average kCal per day ( r s = 0.538, p = 0.047, n = 14), indicating that those with greater physical activity energy expenditure had higher levels of fatigue. A moderate, positive, relationship was found between level and impact of fatigue, and light intensity of activity over the week (IBDF Section 1 r s = 0.391, p = 0.080; IBDF Section 2 r s = 0.365, p = 0.104, n = 21), indicating that those engaged in greater light intensity physical activity experienced higher levels and impact of fatigue. In contrast, a strong, negative, statistically significant relationship was found between time in vigorous activity over the week and impact of fatigue ( r s = −0.812, p = 0.050, n = 6) for those in remission, suggesting that participants undertaking more vigorous physical activity had a lower impact of fatigue. Conclusions: A larger multi-centre study investigating the relationship between fatigue and physical activity and intensity of activity is feasible and warranted. It has the potential to contribute to the modelling and development of a physical activity intervention specifically designed for the management of IBD fatigue.